Naturalized American Citizens and the Presidency - Why Immigrants should be allowed to run for the American Presidency? - Jawahrani, Luv (International Journal of Scientific Research and Management (IJSRM), 2021)
The United States of America is undoubtedly the world's most powerful economic and military powerhouse. This position enables political leaders in the United States to have a profound and decisive impact on world affairs as well as domestic affairs – as a result of the presidential system in the United States, the person elected is responsible for the fates of hundreds of millions of their fellow citizens based on their leadership abilities, personality, and determination. On the other hand, the position of President may only be held by a single person for a maximum of two four-year terms and only by a person who was born in the country, according to the United States Constitution. This prevents a significant number of people, particularly first-generation naturalized immigrants, from gaining access to the highest levels of government. Intimately connected to the ideals of democracy, which are regarded as one of the defining characteristics of the American country, are the American people. Therefore, the validity of that specific constitutional record has been questioned for many years since it severely restricts the rights of certain citizens.